5(2s-4)+2(s-9)=

Simple and best practice solution for 5(2s-4)+2(s-9)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2s-4)+2(s-9)= equation:


Simplifying
5(2s + -4) + 2(s + -9) = 0

Reorder the terms:
5(-4 + 2s) + 2(s + -9) = 0
(-4 * 5 + 2s * 5) + 2(s + -9) = 0
(-20 + 10s) + 2(s + -9) = 0

Reorder the terms:
-20 + 10s + 2(-9 + s) = 0
-20 + 10s + (-9 * 2 + s * 2) = 0
-20 + 10s + (-18 + 2s) = 0

Reorder the terms:
-20 + -18 + 10s + 2s = 0

Combine like terms: -20 + -18 = -38
-38 + 10s + 2s = 0

Combine like terms: 10s + 2s = 12s
-38 + 12s = 0

Solving
-38 + 12s = 0

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '38' to each side of the equation.
-38 + 38 + 12s = 0 + 38

Combine like terms: -38 + 38 = 0
0 + 12s = 0 + 38
12s = 0 + 38

Combine like terms: 0 + 38 = 38
12s = 38

Divide each side by '12'.
s = 3.166666667

Simplifying
s = 3.166666667

See similar equations:

| 4y+5=3y-31 | | 5x-29=3x-5 | | 8(4x-4)=-5-32 | | F(-3)=-3*(3*3)-1 | | -4(2q-7)+6q-7= | | X-14=28+x | | X(x+1)=0.75 | | 89-5x=31x+21 | | 5x+2(x-3)=-15 | | 6(x-6)+6=8x+6 | | 46-4x=6x-4 | | 8+9p+4(11-2p)= | | 40x+10(1.5x)=1500 | | -10n-3+2(5+6n)= | | .33(x-21)=.66 | | x+2+3x-4+2x+6= | | -2=b-150 | | 7+n=-8 | | 9.5-0.315x^2+0.743x=0 | | 2x-13=-81 | | 7-0.33333n=-28 | | 7-0.33333=-28 | | 46.5=3(4+5x) | | 2n+25=45 | | 48=5x+18 | | 2x-3+5(5x+2)= | | 10-3n=12 | | V-5/8=-1/4 | | 3n-10=12 | | f(x)=x^6/(2lnx) | | 32a^3-24a^2+36a=0 | | 1/x=-27/28 |

Equations solver categories